The disappeared [compact disc, unabridged] - Box, C. J. (Box, C. J. Joe Pickett novel, 2018)
Wyoming game warden Joe Pickett tackles two parallel cases involving the disappearance of a prominent British executive and a group of falconers who are being harassed by the feds, a double assignment that catches the attention of a dangerous adversary.